Aesthetic Preference in the Transverse Orientation of the Occlusal Plane in Rehabilitation: Perspective of Laypeople and Dentists - Ana Lidia Carvalho (MDPI AG, 2021)
The present study had a convenience sample with 236 laypeople and 242 dentists who completed an online questionnaire to choose the most attractive image among six pairs for comparison. Control image: symmetric (parallelism between occlusal plane (OP), commissural line (CL), and interpupillary line (IL)). Change of Control, obtaining three images with a 3-degree inclination of the labial commissures. Image A: OP parallel to IL; Image B: OP parallel to CL; Image C: OP at 1.5 degree mean angulation between IL and CL. Non-parametric comparison (IBM© SPSS Statistics vs. 27.0, p < 0.05). The “Dentists” group’s decreasing order of preference (attractiveness) of the images is: Control > A > C > B (p < 0.05). In the “Lay” group, it is: Control > A > (C not ≠ B). Dentists significantly prefer more the Control and Image A than laypeople (p < 0.001). Sex (single exception in laypeople), age, and dentist’s area of activity did not interfere in the perception of attractiveness. Dentists and laypeople preferred the Control when compared to images with CL canted. In the existence of CL inclination, the preference of the groups was the IL as a reference for OP orientation, with the mean angulation or coincident with the CL being considered less aesthetic.